2018
DOI: 10.11113/jt.v80.11484
|View full text |Cite
|
Sign up to set email alerts
|

Amenities Surrounding Commercial Serial Crime Prediction at Greater Valley and Kuala Lumpur Using K-Means Clustering/Pengecaman Kemudahan Awam Sekitar Lokasi Jenayah Kormesial Bersiri Di Lembah Klang Dan Kuala Lumpur Menggunakan Kaedah Gugusan K-Means

Abstract: Serial crime recognition is a critical task. Usually, police officer investigates the serial crime behavior based on their heuristics, evidence or prior information from public. Sometimes, the police officer makes inadequate decision when handling the serial crime problems due to lack of preliminary study on relationship between serial crime and amenities. Therefore, this study explores k-means to identify pattern of surroundings area at serial comersial crime scene. In Malaysia, precisely Selangor, Wilayah Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In the current research, google earth was employed to illustrate the actual and predicted values. Since the outcome of this study showed that eNARX gives a higher accuracy compared to BPTT, and NARX models, the anticipated value from eNARX model has been utilized for displaying the interval amid the real and forecasted values of repetitions three and four [30], [37][38][39][40].…”
Section: Quantum Geographical Information System (Qgis)mentioning
confidence: 99%
“…In the current research, google earth was employed to illustrate the actual and predicted values. Since the outcome of this study showed that eNARX gives a higher accuracy compared to BPTT, and NARX models, the anticipated value from eNARX model has been utilized for displaying the interval amid the real and forecasted values of repetitions three and four [30], [37][38][39][40].…”
Section: Quantum Geographical Information System (Qgis)mentioning
confidence: 99%
“…Seterusnya murid akan menyusuli dengan mengikuti bacaan ayat al-Quran tersebut dan meneruskan ayat selepasnya. Melalui cara ini, ianya dapat membantu murid agar lebih lancar dalam mengingati hafalan (A. H. Abdullah et al, 2005).…”
Section: Mendengarunclassified